Icariin, an Anti-atherosclerotic Drug from Chinese Medicinal Herb Horny Goat Weed - Fang, Jian; Zhang, Yongjun (Frontiers in Pharmacology, 2017)
Icariin is a major bioactive pharmaceutical constituent isolated from Chinese medicine Horny Goat Weed with potent cardiovascular protective functions. Emerging evidence in the past decade has shown that Icariin possesses multiple atheroprotective functions, through multiple mechanisms, including attenuating DNA damage, correcting endothelial dysfunction, inhibiting the proliferation and migration of smooth muscle cells, repressing macrophage-derived foam cell formation and inflammatory responses, as well as preventing platelet activation. All of these protective effects, combined with its lipid-modulatory effects, contribute to the broad atheroprotective effects of Icariin. In this review, we will summarize the anti-atherosclerotic properties of Icariin and highlight future perspectives in developing Icariin as a promising anti-atherosclerotic drug.